Nove anos (2000 – 2008) de experiência com o uso de hidroxiuréia em pacientes adultos e pediátricos com anemia falciforme no ambulatório de hematologia da Fundação Hemopa - MAGALHÃES, Renata da Costa (2023)
Hydorxyurea (HU) has been studied in recent years for their ability to increase levels of Fetal Hemoglobin (HbF) in patients with sickle cell disease (SCA) and is useful in protecting against vaso-occlusive complications. This study evaluated the impact of this drug on life quality of these patients by reducing hospitalizations, transfusion requeriments, painful episodes and infections, understand the causes of treatment interruption, death and levels of hemoglobin (Hb) and HbF after initiation of HU. It was performed a retrospective study of 25 adults and pediatrics medical records with SCA enrolled in the Clinic Foundation Center of Hemotherapy and Hematology of Pará (Hemopa) in the period 2000 to 2008. Of 25 patients, 4 had drug toxicity by elevation of hepatic enzymes, leucopenia and thrombocytopenia, stopping the medication until the normalization of their levels. There are case of SCA complications as hypersplenism, cholelithiais and stoke before HU introduction. Most of sickle cell drug therapy initiated before 18 years old. There was a reduction of transfusion requirements, infections and hospitalizations after the onset of HU, as well as the increase in mean Hb and HbF, however, the frequency of painful episodes increased in some patients. It was concluded that this drug increases the levels of HbF and is useful in improving the life quality of these patients, with few adverse effects, which are dose dependent, suggesting that HU has the potential to reduce mobidity and mortality. Since most users are in the pediatric population, there is a need for the completion of this study on this impact on growth and development of these children.